When Sophie gets angry-- : really, really angry-- - Bang, Molly (New York : Blue Sky Press, 1999)
When Sophie gets angry, she goes outside and runs, cries, climbs her favorite tree--and then, calmed by the breeze, she is soon ready to go back home.
Wilson's Children, October 2010.
School Library Journal starred, January 1999.
Notable/Best Books (A.L.A.), January 2000.
Five Owls, March 1999.
Book Links (A.L.A.), December 2002.
Publisher's Weekly, January 1999.
Keywords: Anger -- Fiction; Family life -- Fiction; Caldecott honor book